'The Potential for Blockchain and Artificial Intelligence to Enhance the Transport Sector - Hargroves, Charlie; Conley, Daniel; Stantic, Bela (2019)
This paper outlines research that explores a range of digitally-driven opportunities and challenges in seeking to get cities moving and functioning better; with a focus on the application of Artificial Intelligence and Blockchain technologies. The paper identifies specific potential applications and outlines where such technology can provide tangible benefits for the transport sector and the associated policy and management structures. Specific benefits explored include cost savings (such as digital payment mechanisms, virtual toll collection and congestion charging, capital deferment through greater network utilisation); time savings (from improved transport network operation and management processes); improved operations (such as real-time pay-as-you-drive systems with network differential pricing ability); improved safety (from less collisions and reduced impacts); improved user experience (such as improved platforms and automated payments for parking and bookings); and improved freight and logistics (such as secure storage of time-stamped travel-related data). The paper presents a set of industry partner-preferred use cases such as congestion management, road user pricing, asset management, mobility-as-a-service and freight logistics. The paper outlines specific opportunities for Artificial Intelligence and Blockchain technology to provide value to transport agencies and service providers, either individually or in combination. The paper highlights risks and rewards for the transport sector, including a further review of early findings from the application of such technologies in transport sectors around the world. This research has been developed with funding and support provided by Australia’s Sustainable Built Environment National Research Centre (SBEnrc) and its partners.